The emergence of texture - Sliver, Sean (Journal of the History of Ideas)
Crucial to accounts of complexity is the history of the concept of emergence. Pride of place is generally given to G. E. Lewes, who in 1879 offered a theory of (3z(Bemergents,(3y (Bof the unpredictable and incommensurate effects which follow from the crossing of causes. This essay recovers an earlier tradition; it focuses on experiments in seventeenth-century materials science, which explain emergent properties through an appeal to microstructural (3z(Btexture.(3y (BA full appreciation of the modern turn to complexity, of our own ecological embeddeness and the interrelationship of things, requires therefore a return to the warp and weft of seventeenth-century artisanal practice.- Reproduced s
Keywords: Alina Szczesniak, Emergence, Food Science, Weaving